The Possibilities for Better Project Tracking based on the New Developments of the Precedence Diagramming Method. (2016) - Isaac, S.; Hajdu, M.
Abstract: Tracking a schedule is one of the most challenging tasks for the project control personnel. The problems they face arise as a consequence of the limitations of the existing Precedence Diagramming Method, namely that activities are assumed to be linear and that precedence relations control only the end-points of the activities. Recent developments of the Precedence Diagramming Method such as continuous and point-to-point relations give the opportunity to control as many points as necessary during the tracking process. However, a method that helps to create as-built production-time activity functions is still missing. The result of this paper is the development of new types of constraints that can be used to monitor the activities in progress, and that allow one to re-calculate the plan based on as-built data.